Local Democracy, Rural Community, and Participatory School Governance - Gaysu R. Arvind (Journal of Research in Rural Education, 2009)
This article considers the indigenization of democracy in India by conceptualizing participatory deliberative decisionmaking practice as a tool to strengthen the functioning of local schools and to enhance democratic responsiveness within communities. Drawing on case-studies of bottom-up approaches to school governance, this study examines an array of innovative participatory governance practices that have emerged in diverse rural settings to make the state more responsive and accountable to the education of marginalized children. The author argues that these practices have enabled a fuller realization of people's rights and have enhanced their ability to influence larger institutions and policies affecting the schooling and lifeoptions of their children.